Genome-Wide Association Mapping of Virulence Genes in Wheat Karnal Bunt Fungus Tilletia indica Using Double Digest Restriction-Site Associated DNA-Genotyping by Sequencing Approach - Shakouka, Mohamad Ayham; Gurjar, Malkhan Singh; Aggarwal, Rashmi; Saharan, Mahender Singh; Gogoi, Robin; Bainsla Kumar, Naresh; Agarwal, Shweta; Kumar, Tej Pratap Jitendra; Bayaa, Bassam; Khatib, Fateh (Frontiers in Microbiology, 2022)
Tilletia indica is a quarantine fungal pathogen that poses a serious biosecurity threat to wheat exporting countries. Acquiring genetic data for the pathogenicity characters of Tilletia indica is still a challenge for wheat breeders and geneticists. In the current study, double digest restriction-site associated -DNA genotyping by sequencing was carried out for thirty-nine Tilletia indica isolates collected from different locations in India. The generated libraries upon sequencing were with 83,346,759 raw reads in average, and 151x2 nucleotides read length. The obtained bases per read ranged from 87 Mb in Ti 25 to 1708 Mb in Ti 39, with 505 Mb in average per read. Trait association mapping was performed using 41,473 SNPs, infection phenotyping data, population structure and Kinship matrix, to find single nucleotide polymorphisms (SNPs) linked to virulence genes. Population structure analysis divide T. indica population in India into three subpopulations with genetic mixing in each subpopulation. However, the division was not in accordance with the degree of virulence. Trait association mapping revealed the presence of thirteen SNPs associated with virulence. Using sequences analysis tools, one gene (g4132) near a significant SNP was predicted to be an effector, and its relative expression was assessed and found up-regulated upon infection.